Perturbation-Induced Stepping Post-stroke: A Pilot Study Demonstrating Altered Strategies of Both Legs - Martinez, Katherine M.; Rogers, Mark W.; Blackinton, Mary T.; Cheng, M. Samuel; Mille, Marie-Laure (Frontiers in Neurology, 2019)
Introduction: Asymmetrical sensorimotor function after stroke creates unique challenges for bipedal tasks such as walking or perturbation-induced reactive stepping. Preference for initiating steps with the less-involved (preferred) leg after a perturbation has been reported with limited information on the stepping response of the more-involved (non-preferred) leg. Understanding the capacity of both legs to respond to a perturbation would enhance the design of future treatment approaches. This pilot study investigated the difference in perturbation-induced stepping between legs in stroke participant and non-impaired controls. We hypothesized that stepping performance will be different between groups as well as between legs for post-stroke participants. Methods: Thirty-six participants (20 persons post-stroke, 16 age matched controls) were given an anterior perturbation from three stance positions: symmetrical (SS), preferred asymmetrical (PAS−70% body weight on the preferred leg), and non-preferred asymmetrical (N-PAS−70% body weight on the non-preferred leg). Kinematic and kinetic data were collected to measure anticipatory postural adjustment (APA), characteristics of the first step (onset, length, height, duration), number of steps, and velocity of the body at heel strike. Group differences were tested using the Mann-Whitney U-test and differences between legs tested using the Wilcoxon signed-rank test with an alpha level of 0.05. Results: Stepping with the more-involved leg increased from 11.5% of trials in SS and N-PAS up to 46% in PAS stance position for participants post-stroke. Post-stroke participants had an earlier APA and always took more steps than controls to regain balance. However, differences between post-stroke and control participants were mainly found when stance position was modified. Compare to controls, steps with the preferred leg (N-PAS) were earlier and shorter (in time and length), whereas steps with the non-preferred leg (PAS) were also shorter but took longer. For post-stroke participants, step duration was longer and utilized more steps when stepping with the more-involved leg compared to the less-involved leg. Conclusions: Stepping with the more-involved leg can be facilitated by unweighting the leg. The differences between groups, and legs in post-stroke participants illustrate the simultaneous bipedal role (support and stepping) both legs have in reactive stepping and should be considered for reactive balance training.